HABITS SHOULD BE CHANGE, JUST LIKE SEASON CHANGES: VASANT RITU REGIMEN - Swami Devika; Sharma Anita; Pali Vibha (International Journal of Applied Ayurved Research, 2020)
The preservation of health is easier than the cure of the disease. The objective of Ayurveda, is to protect health of the healthy and to alleviate disorders in the diseased. To fulfill the first objective i.e., to keep the body away from the disease, many regimen like the dincharya (daily regimen), ratricharya (night regimen), ritucharya (seasonal regimen), sadvritta (code of conduct), have been mentioned in the classics of Ayurveda. The change in ahara (diet) and vihara (lifestyle) in response to change in climatic condition is Ritucharya. The year is divided into two ayana (solstices) depending upon the direction of movement of sun; Uttarayana (northern solstice) and Dakshinayana (southern solstice). Each ayana is divided into three ritu. In this manner there are total six ritu- shishira, vasant, grishma, varsha, sharada and hemanta. Vasant ritu (spring season) comes under uttarayana, when sun is very powerful than moon, among three dashers (vata, pitta, kapha), kapha gets aggravated during vasant ritu, strength of person is taken away day by day in vasant ritu. Here in this article emphasis is given in this particular season and preventions to be taken to avoid equilibrium from health.